Desenvolvimento de métodos para o preparo de amostras de fertilizantes visando à determinação de cobre, cádmio e chumbo por espectrometria de absorção atômica com chama - Lima, Alexandre de Faria (2011)
The chemical fertilizer used in crops to meet the nutritional deficiencies of soil and consequently increase its fertility and productivity, can be a major responsible for contaminating the soil with heavy metals. In this way, this work presents an optimization study to extract copper, lead and cadmium in samples of mineral fertilizer (inorganic) using an ultrasonic bath for the sample preparation and determination by a flame atomic absorption spectrometry, comparing the results obtained by the proposed method with the official method designated by the Brazilian Ministry of Agriculture (Ministério da Agricultura, Pecuária e Abastecimento - MAPA). For the development of this work, different parameters were evaluated, such as the sonication time, the sample mass, composition and concentration of the extracting solution, in order to obtain the best condition for extraction and analytical determination of metals. After defining some parameters, comparison tests were performed using extraction by vortex agitation with ultrasonic bath in order to assess possible changes in extraction efficiency. A central composite design (PCC) comprising a two-level factorial design with three variables (23), plus a central point in triplicate and even experiments in six axial points (± α1), totaling 17 experiments was then performed to optimize the method employing a sample certified by the National Agency of Promotion of Fertilizers (Agência Nacional de Difusão de Adubos, ANDA). Other five samples, two of them certified by ANDA, were also analyzed using the optimized conditions. The favorable analytical conditions were 70 mg of sample, 5 min sonication and 50% (v/v) HNO3 as extractor solution, which provided efficiency extraction higher than 80% in most cases. The proposed method of sample preparation offers as main advantages the fastness, versatility and reduction of the volume of acids and sample, and then diminishes waste generation.